Perfil bioquímico da água de coco de coqueiros de região não litorânea Biochemical profile of coconut water from coconut palms planted in an inland region - Renata Vigliar; Vera L. Sdepanian; Ulysses Fagundes-Neto (Elsevier, 2006)
OBJETIVO: Analisar o perfil bioquímico da água de coco de coqueiros-anões plantados em região não litorânea, no período de maturação (sexto ao nono mês). MÉTODOS: Selecionaram-se por sorteio oito de 15 coqueiros plantados em região não litorânea, e os cocos foram enviados ao laboratório para extração e análise da água de coco. Avaliou-se glicose, eletrólitos, proteínas totais, osmolaridade, e identificaram-se açúcares da água de coco, em um total de 45 cocos, do sexto ao nono mês de maturação. RESULTADOS: A análise da água de coco do sexto ao nono mês não demonstrou diferença da mediana da concentração do sódio (3 mEq/L; 2 e 3), glicose (0,6 g/L; 0,3 e 17,3) e proteínas totais (9 g/L; 6 e 12); houve redução na concentração de potássio (64 mEq/L; 46 e 99), cálcio (6,5 mmol/L; 5 e 8,5), magnésio (8 mmol/L; 3,9 e 9,8), cloro (38,5 mEq/L; 30 e 48,7) e osmolaridade (419 mOsmol/L; 354 e 472). Com relação aos açúcares identificados por cromatografia em papel, observou-se aumento da concentração de frutose (68 mg/µL; 44 e 320) e de glicose (299 mg/µL; 262 e 332) e redução na concentração de sacarose (340 mg/µL; 264 e 390) do sexto ao nono mês. CONCLUSÕES: O perfil bioquímico da água de coco variou durante a maturação do fruto, observando-se redução da concentração de potássio, cálcio, magnésio, cloro e osmolaridade. Segundo a cromatografia em papel descendente, observou-se aumento da concentração de frutose e de glicose, bem como redução da concentração de sacarose. OBJECTIVE: To analyze the biochemical profile of coconut water from dwarf coconut palms planted in non-coastal regions, during the maturation period (sixth to ninth month). METHODS: Eight of 15 coconut palms planted in a non-coastal region were selected by lots and their coconuts sent to a laboratory for extraction and analysis of the coconut water. Coconut water from a total of 45 coconuts, from the sixth to ninth months' maturity, were analyzed to measure glucose, electrolytes, total proteins and osmolarity and to identify the sugars contained. RESULTS: The analysis of coconut water from the sixth to ninth month did not find any differences in the median concentrations of sodium (3 mEq/L; 2 and 3), glucose (0.6 g/L; 0.3 and 17.3) or total proteins (9 g/L; 6 and 12), but detected a reduction in the concentration of potassium (64 mEq/L; 46 and 99), calcium (6.5 mmol/L; 5 and 8.5), magnesium (8 mmol/L; 3.9 and 9.8), chloride (38.5 mEq/L; 30 and 48.7) and osmolarity (419 mOsmol/L; 354 and 472). With relation to the sugars, identified by chromatography on paper, an increase was observed from the sixth to the ninth month in the concentration of fructose (68 mg/µL; 44 and 320) and glucose (299 mg/µL; 262 and 332) and in conjunction with a concentration of sucrose (340 mg/µL; 264 and 390). CONCLUSIONS: The biochemical profile of coconut water varied as the coconuts matured, observing reductions in the concentration of potassium, calcium, magnesium, chloride and osmolarity. Descending paper chromatography revealed an increase in the concentration of fructose and glucose and also a reduction in the concentration of sucrose.